2018
DOI: 10.1007/s00604-018-2983-3
|View full text |Cite
|
Sign up to set email alerts
|

Impedimetric determination of Staphylococcal enterotoxin B using electrochemical switching with DNA triangular pyramid frustum nanostructure

Abstract: An electrochemical switching strategy is presented for the sensitive determination of Staphylococcus enterotoxin B (SEB). It is based on the use of DNA triangular pyramid frustum nanostructure (TPF) consisting of (a) three thiolated probes, (b) one auxiliary probe, and (c) an aptamer against SEB. The TPF was assembled on the gold electrode, with the SEB aptamer designed on top of the TPF. The electron transfer to hexacyanoferrate acting as an electrochemical probe is strongly inhibited in the TPF-modified elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Inspired by this approach, Xiong's group developed an electrochemical biosensor to detect staphylococcal enterotoxin B (SEB), a leading cause of foodborne illnesses, in milk samples. 266 TPF−ET transformation occurred in the presence of SEB and was made observable by changes in Faradaic impedance.…”
Section: Chemosensors and Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by this approach, Xiong's group developed an electrochemical biosensor to detect staphylococcal enterotoxin B (SEB), a leading cause of foodborne illnesses, in milk samples. 266 TPF−ET transformation occurred in the presence of SEB and was made observable by changes in Faradaic impedance.…”
Section: Chemosensors and Biosensorsmentioning
confidence: 99%
“…The authors found a linear relation between Faradaic impedance response and cocaine concentration for concentrations between 1.0 nM and 2.0 μM. Inspired by this approach, Xiong’s group developed an electrochemical biosensor to detect staphylococcal enterotoxin B (SEB), a leading cause of foodborne illnesses, in milk samples . TPF–ET transformation occurred in the presence of SEB and was made observable by changes in Faradaic impedance.…”
Section: Applications Of Aptamers On Nucleic Acid Nanostructuresmentioning
confidence: 99%
“…Our previous work has been done on electrochemical detection of SEB based on DNA nanostructured probe. [26][27][28][29] DNA nanomaterials have excellent structural properties, but assembly is complex. [26][27][28] Impedance method is simple and convenient, but it is greatly disturbed by food substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] DNA nanomaterials have excellent structural properties, but assembly is complex. [26][27][28] Impedance method is simple and convenient, but it is greatly disturbed by food substrate. 29 Thus, the purpose of this work is to develop a sensitive and easy aptamer-based electrochemical sensor, capable of reagentless detection of SEB with high sensitivity, selectivity, and extremely broad dynamic ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, various analytical methods have been employed for the detection and quantification of SE content in food, water, and even bodily fluids, such as serum. These techniques include enzyme-linked immunosorbent assays (ELISAs), , lateral flow platforms, polymerase chain reactions (PCRs), chemiluminescent assays, colorimetric sensors, , electrochemical assays, , and surface-enhanced Raman scattering assays . Most of these detection strategies demand complicated instruments, strict laboratory conditions, and trained personnel.…”
Section: Introductionmentioning
confidence: 99%